(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Introduction of numerous Kazakh words to the translated text is directly related to the characteristics of national picture of the world, and reflection of determination of national identity of Kazakh people in foreign audience. Kazakh words reveal the history, language, customs, culture, religious beliefs, specifics of lifestyle, landscape, etc. In the process of translation, aesthetic contradictions of systemic nature occur. Any systemic discrepancy is burdened by additional connections. Possessing a certain «condition of stability, it also develops certain conditions for instability, and generates «systemic» contradictions. The process of reproduction of the original, in our opinion, is also conditioned by the objective law of divergence and convergence of literary forms. Translation as a new combination of aesthetic codes undergoes conjugation changes, which counteracts a disorderly divergence. Thus, the laws of aesthetic interference come into force and interaction. From this point of view, translations of works by Kazakh writers and poets into English are a vivid example of interpretation of such laws of literary cohesion.